Improvement of the power factor on the distribution line feeder Sutami 23 Lampung using capacitor bank and SVC with ETAP 12.6 simulation - Alvin Harista Rahman; Ahmad Hidayahtullah; Afrida Nurul Ulfa; Rizal Zulfiqri Ahmad; Jimmy Trio Putra (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2021)
A good power distribution rate is the key to the success of electric power service providers in fulfilling consumer rights. A poor power distribution rate will cause a lot of losses, both for consumers and providers. The power distribution rate is closely related to the power factor value (PF). Low PF should be avoided to get a good power distribution rate. Sutami 23 Lampung feeder data shows 216 buses with a PF below the SPLN 70-1: 1985 standard, which is 0.85, so a PF correction is needed. In this research, PF corrections have been made with the ETAP simulation method for two kinds of components, namely capacitor bank, and SVC (static VAr compensator). The results showed that installing the capacitor bank is more recommended than SVC because the impact of installing the capacitor bank for PF correction is bigger than SVC. Capacitor bank can raise the PF from 0.82 to 0.98, while SVC can only raise the PF from 0.82 to 0.91. In addition, the investment cost for installing a capacitor bank is also much cheaper than SVC, with a cost difference of 1,932,000.250 IDR. Salah satu cara yang dapat dilakukan untuk memperbaiki tingkat penyaluran daya adalah dengan melakukan upaya perbaikan faktor daya (PF). Standar SPLN 70-1: 1985 menyatakan nilai PF minimal adalah 0,85. Data Penyulang Sutami 23 Lampung menunjukkan terdapat 216 bus dengan nilai PF di bawah 0,85 sehingga diperlukan adanya upaya perbaikan. Pada penelitian ini telah dilakukan perbaikan nilai PF dengan menggunakan metode simulasi ETAP 12.6 melalui kapasitor bank dan static VAr compensator (SVC). Hasil menunjukkan bahwa komponen kapasitor bank lebih direkomendasikan untuk memperbaiki nilai PF Penyulang Sutami 23 Lampung karena dengan nilai kapasitas daya kVAr yang sama, tercatat nilai PF baru hasil perbaikan dari pemasangan kapasitor bank memiliki nilai yang lebih tinggi daripada nilai PF baru yang dihasilkan dari pemasangan SVC. Pemasangan kapasitor bank mampu memperbaiki nilai PF dari 0,82 menjadi 0,98. Sedangkan, untuk pemasangan SVC mampu memperbaiki nilai PF dari 0,82 menjadi 0,91. Selain itu, total biaya investasi yang dibutuhkan untuk pemasangan kapasitor bank juga lebih murah jika dibandingkan dengan SVC yaitu memiliki selisih biaya sebesar Rp1.932.000.250,-.